Pengembangan E-Modul Berbasis Book Creator pada Materi Sebaran Flora dan Fauna Dunia Kelas XI SMA Negeri 1 Gondang - Fadhila Eka Meyliana; Hendra Pratama (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The purpose of this study is to determine the level of validity and effectiveness of the e-module based on book creator on the distribution of flora and fauna in the world for class XI SMA Negeri 1 Gondang. This study uses the R&D method with the Borg and Gall model. The main subjects in this study were students in class XI-1 SMA Negeri 1 Gondang with a total of 39 students. The results of this study indicate that the results of the media expert validation test were 98%, the material expert validation was 95%, the language expert validation was 98%, and the subject teacher validation was 95%. The results of the effectiveness test through the Paired Sample t-Test showed a significance value of 0.000 which is less than 0.05. Thus, the alternative hypothesis is declared accepted and shows that there is a difference in student learning outcomes before and after using the e-module. So, it can be concluded that the e-module based on book creator on the distribution of flora and fauna in the world is valid according to experts and effective in improving student learning outcomes.